The summer hydrographic structure of the Hanna Shoal region on the northeastern Chukchi Sea shelf: 2011–2013. (October 2017) - Weingartner, Thomas; Fang, Ying-Chih; Winsor, Peter; Dobbins, Elizabeth; Potter, Rachel; Statscewich, Hank; Mudge, Todd; Irving, Brita; Sousa, Leandra; Borg, Keath
Abstract: We used shipboard and towed CTD, current meter, and satellite-tracked drifter data to examine the hydrographic structure in the northeastern Chukchi Sea in August–September of 2011, 2012, and 2013. In all years the densest winter water was around and east of Hanna Shoal. In 2012 and 2013, a ~ 15 m deep layer of cold, dilute meltwater overlaid the dense water north of the shelf region between ~ 71.2 and ~ 71.5°N. A front extends from the southwest side of Hanna Shoal toward the head of Barrow Canyon, separated meltwaters from warmer, saltier Bering Sea Summer Waters to the south. Stratification was stronger and the surface density variances in the meso- and sub-mesoscale range were higher north of the front than to the south. No meltwater or surface fronts were present in 2011 due to a very early ice retreat. Differences in summer ice cover may be due to differences in the amount of grounded ice atop Hanna Shoal associated with the previous winter's regional ice drift. Along the north side of Hanna Shoal the model-predicted clockwise barotropic flow carrying waters from the western side of the Shoal appears to converge with a counterclockwise, baroclinic flow on the northeast side. The baroclinic tendency is confined to the upper 30 m and can include waters transported from the shelfbreak. The inferred zonal convergence implies that north of the Shoal: a) near-surface waters are a mixture of waters from the western and eastern Chukchi Sea and b) the cross-isobath pressure gradient collapses thereby facilitating leakage of upper layer waters northward across the shelf.